Per una educazione illuministica. I «Racconti morali» di Giambattista Biffi: le fonti (ACME, 2021)
The article focuses on Giambattista Biffi (1736-1807), an Enlightenment nobleman and thinker of Cremona, member of the Accademia dei Pugni, and on the analysis of his unpublished autograph Racconti morali ad uso d’un fanciullo, held in the State Library of Cremona. These novellas were written with a pedagogical purpose for Daniele Ala, firstborn of Biffi’s friend marquis Gian Francesco Ala. After considering the family’s background and the historical context in which the novellas were composed – the period of the Habsburg reforms – the author dates them and identifies the press sources, both Italian and foreign, from which Biffi based the plot of the stories. Finally, she analyses the inspiring Enlightenment theory of virtue, seen as social utility for people’s wellbeing and happiness.